Early Nutrition and Growth until the Corrected Age of 2 Years in Extremely Preterm Infants - Hiltunen H; Löyttyniemi E; Isolauri E; Rautava S. (My University, 2022)
Abstract
BACKGROUND:
Extremely preterm birth is associated with a high risk of extrauterine growth retardation, which has been linked with adverse developmental outcomes.
OBJECTIVE:
We investigated whether nutritional management during the first 7 days of life affects growth patterns until the corrected age of 2 years in extremely preterm infants.
STUDY DESIGN:
A retrospective study of 78 extremely preterm (<28 weeks' gestation) neonates was conducted. Data regarding parenteral and enteral intake of energy, protein, lipids, and carbohydrates during the first 7 days of life were collected from patient records. The outcome measures included weight, height, and head circumference with Z scores at term-equivalent age and the corrected ages of 1 and 2 years. Analyses were performed with hierarchical-linear mixed models.
RESULTS:
Nutritional intake during the first week of life did not reach the current recommendations. The total energy intake during the first 7 days of life was statistically significantly associated with weight, length, and head circumference until the corrected age of 2 years after adjusting for potential confounding factors. Individual macronutrient intake displayed no association with growth patterns.
CONCLUSIONS:
Energy intake during the first 7 days of life is associated with growth until the corrected age of 2 years. These results provide support for the aggressive early nutritional management of extremely preterm infants.